A liminal stage after predictive testing for Huntington disease. Issue 8 (13th January 2017) - Gargiulo, Marcela; Tezenas du Montcel, Sophie; Jutras, Marie France; Herson, Ariane; Cazeneuve, Cecile; Durr, Alexandra
Abstract : Background: Following predictive testing for Huntington disease (HD), knowledge of one's carrier status may have consequences on disease onset. Our study aimed to address two questions. First, does knowledge of being a carrier of the pathological HD mutation trigger onset of the disease? Second, does this knowledge influence self-awareness and allow carriers to identify signs and symptoms of disease onset? Methods: Between 2012 and 2015, 75 HD mutation carriers were examined using the Unified Huntington's Disease Rating Scale (UHDRS) motor score. Onset estimation made with the disease burden score was compared with UHDRS findings. We collected qualitative data with questionnaires and semistructured interviews. Results: 38 women and 37 men, aged 43.7 years±10.5 (20–68), were interviewed after a mean delay between test and study interview of 10.5 years±4.7 (from 4 to 21 years). Estimation of age at onset was 4.5±8.5 years earlier than data-derived age at onset. Participants were categorised according to their motor score: scores <5 were premanifest (n=35), and scores >5 were manifest carriers (n=40). Self-observation was a major preoccupation for all, independent of their clinical status (82% vs 74%, p=0.57). Among manifest carriers, 56% thought they showed symptoms, but only 33% felt ill. Interestingly, this was also observed in those without motor signs (20% and 9%). Being a mutation carrier did not significantly facilitate recognition of motor signs. Interviews with premanifest carriers allowed the burden of self-observation to be illustrated despite lack of motor signs. Conclusions: Estimating age at onset based on disease burden score may not be accurate. The transition to disease was experienced as an ambiguous or liminal experience. The view of mutation carriers is not always concordant with medical onset estimation, highlighting the difficulties involved in the concept of onset and its use as an outcome in future disease-modifying trials.